Development and Evaluation of a Digitized Teaching-Learning Package for Grade 7 Geometry - Dela Torre, Jonabeth; Erfe, Mary Rose; Sugatamama, Shairalyn; Paz, Skezeer John (Ilmu Inovasi Nusantara, 2025)
The study developed and evaluated a digitized teaching-learning package for Geometry 7, adapted from the K-12 curriculum, that addressed the diverse needs of the students crucial in today’s educational context. Development and evaluation and quasi-experimental research design utilizing the ADDIE model were used to develop and examine the effects of interventions and to guide the development and evaluation of effective digitized teaching-learning materials. The package presented detailed lesson plans with developed learning modules, teacher’s guides, and PowerPoint presentations integrated with the GeoGebra application. The evaluation of the package based on content, instructional, and technical quality attained an excellent rating. The package’s contents of each activity were relevant, well-organized, evaluative, illustrative, student-suited, and curriculum-aligned—the instructional materials presented clear and efficient explanations. Moreover, the technical presentation of the PowerPoint lessons was logical and sequential, and GeoGebra was integrated effectively. The study involved two regular sections of a public school, in which one section served as the group that utilized the package while the other group did not. Researchers determined the effectiveness of the package by comparing the posttest scores of both groups and the pretest and posttest scores of the experimental group. The evaluations significantly improved the experimental group students’ geometric conceptualization and problem-solving skills. The results from implementing the package underscore its potential to enhance students' performance. By incorporating similar instructional materials, educational institutions could provide students with engaging and compelling learning experiences in Geometry